Asymmetrical recognition and processing of double-strand breaks formed during DNA replication - Matthew J. Johnson; Michael T. Kimble; Seoyeon Jeong; Aakanksha Sane; Lorraine S. Symington (Proceedings of the National Academy of Sciences, 2025)
DNA end resection to generate 3′ single-stranded DNA (ssDNA) overhangs is the first step in homology-directed mechanisms of double-strand break (DSB) repair. While end resection has been extensively studied in the repair of endonuclease-induced DSBs, little is known about how resection proceeds at DSBs generated during DNA replication. We previously established a system to generate replication-dependent double-ended DSBs at the sites of nicks induced by the Cas9 D10A nickase in the budding yeast genome. Here, we suggest that these DSB ends form in an asymmetric manner, with one being blunt or near blunt and the other bearing a 3′ ssDNA overhang of up to the size of an Okazaki fragment. We find that Mre11 preferentially binds blunt ends and is required to evict Ku from these DSB ends and to promote end resection. In contrast, the ends predicted to have 3′ overhangs have minimal Ku binding, and resection at these break ends can proceed in a mostly Mre11-independent manner through either the Exo1 or Dna2-Sgs1 long-range resection mechanisms. These findings indicate that resection proceeds differently at replication-dependent DSBs than at canonical DSBs and reveal that Ku selectively binds blunt ends, potentially explaining why replication-dependent DSBs are poorly repaired by nonhomologous end joining.